HUBUNGAN ANTARA KADAR HEMOGLOBIN (HB) DENGAN PRESTASI BELAJAR MAHASISWA KEBIDANAN YANG TINGGAL DI ASRAMA PENDIDIKAN STIK BINA HUSADA PALEMBANG - Tri Sartika (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Anemia in adolescents can cause physical growth retardation, behavioral and emotionaldisorders. This can affect the growth process and development of brain cells so that it can causedecreasing on imun system, weak easily and hunger, learning concentration disturbed, decreasedlearning achievement and can lead to low work productivity. According to data from Riskesdas in 2013,the prevalence of anemia in female teenagers aged 10-18 years was 57.1% and aged 19 - 45 years was39.5%. Women have the highest risk to get anemia, especially in female teenagers. This study aims todetermine the relationship between hemoglobin level (Hb) and learning achievement of midwiferystudents who live at Educational Dormitory of STIK Bina Husada Palembang in 2017. This study wasquantitative with cross sectional approach. The study sample amounted to 84 respondents. The studyinstrument was Set of Hb Sahli and Checklist. Data analysis was univariate and bivariate with chi-squaremethod. The study was conducted on 12 – 23 June 2017. The study results showed there was significantrelationship of hemoglobin levels variable with the learning achievement of Midwifery Students who livedat Educational Dormitory of STIK Bina Husada Palembang in 2017, with p value = 0.005 (? ? 0.05).The value of OR = 9,000 meant that respondents with Un-normal Hb had a chance 9 times to have Lesslearning achievement, compared with respondents with Normal Hb levels. It is expected that femaleteenagers will always maintain the reproductive health and actively seek information about reproductivehealth to detect early if abnormal (pathological) conditions are found